Adolescent gambling and impulsivity: Does employment during high school moderate the association?. (September 2016) - Canale, Natale; Scacchi, Luca; Griffiths, Mark D.
Abstract: The aim of the present study was to examine the potential moderating relationships between adolescent gambling and impulsivity traits (negative urgency, positive urgency, lack of premeditation, lack of perseverance and sensation seeking) with employment status. High-school students (N = 400; 69% male; mean age = 18.35 years; SD = 1.16; past year gamblers) were surveyed to provide data on impulsivity and employment. Multiple linear regression analysis was applied to examine associations with gambling and related problems. Positive urgency was associated with stronger scores of both gambling frequency and problem gambling. Students in employment had substantially higher frequency of gambling and greater problem gambling. Moreover, the combination of having a job and low perseverance was associated with a particularly high frequency on gambling. These findings further support the importance of positive urgency and employment status in adolescent gambling. The study highlights unique moderating relationship between gambling and lack of perseverance with employment status. Youth with a low perseverance and having a job may have particular need for interventions to reduce gambling. Highlights: Little is known about factors involved in the link between impulsivity and gambling Environmental factors may explain links between impulsivity and adolescent gambling The study examined moderating links between impulsivity, gambling and having a job Having a job may be a risk factor for adolescents who gamble A moderating link between gambling and lack of perseverance with a job was found